9- The First Ten Years: A Review of African Sociological Review, 1997-2006 - Oloyede, Olajide (African Sociological Review, 2006)
Scholarly journals are acknowledged as the mainstays of scientific communication and academics publish in them for promotion, recognition among peers and mobility in academia. The scrutiny and assessment of academic journals is therefore vital to the scientific academic community. Such scrutiny is part of the organisation of scholarly publication and allows insights into the publishing performance of a journal. It is within this academic practice that this paper reviewed the contributions to the African Sociological Review, which is now in its tenth year. Examined as part of the review were the type of papers published, the quantity of each type, the authors of the papers, and the institutional affiliations of the authors and the country of origin of the papers. The analyses showed that the African Sociological Review could best be regarded as a journal of commentary, mostly with a theoretical bent, extended essays with carefully built arguments and qualitative empirical articles. The review therefore drew the conclusion that the journal falls into the category of social science journal that has been described as a ‘literary’ type than the ‘normal science’ type.